Efisiensi Daya Protokol Quantize and Forward Pada Sistem Komunikasi Kooperatif Multi-relay - Nasaruddin Nasaruddin; Rony Kurnia; Ramzi Adriman (Universitas Syiah Kuala, 2017)
One of effective diversity techniques to combat fading on wireless channel is a cooperative communication system in which a source sends information through several relays and then forward it to a destination. A cooperative communication system has shown increased the system performance and reduced the energy consumption. However, it depends on the used relay mechanism that is relay protocols such as quantize and forward (QF) and amplify and forward (AF). In the previous research, energy efficiency of AF relay has investigated for a single-relay cooperative system, but multi-relay is more practical. Therefore, this research focuses on power efficiency in multi-relay cooperative communication system using QF protocol. The research method used is mathematical analysis and computer simulation for outage probability and power efficiency in the multi-relay QF. Simulation result found that multi-relay QF system could provide a high power efficiency, but the efficiency is reduced when the distance ratio increases. Power efficiency can be increased by adding the number of relays in the system. A comparison of power efficiency for QF and AF protocols has simulated, in which power efficiency of multi-relay QF is higher than that of multi-relay AF at distance ratio and power transmit. Thus, multi-relay QF system can provide high performance and power efficiency in the cooperative communication system.